2013
DOI: 10.3109/14397595.2013.854054
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis of the hand: a five-year longitudinal analysis of clinical and radiographic findings

Abstract: Our study showed that there was a marked progression in hand deformities in RA patients over a 5-year period. In order to assist RA patients in performing the activities of daily living, medical and rehabilitative interventions should target the restoration of functional loss through joint destruction as well as the prevention of disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…In a 5-year follow up of RA hands, we similarly found progression of joint destruction regardless of disease activity [23]. Our results indicated that joint destruction might be progressing in patients in remission who show synovitis on MRI-MIP images.…”
Section: Discussionsupporting
confidence: 80%
“…In a 5-year follow up of RA hands, we similarly found progression of joint destruction regardless of disease activity [23]. Our results indicated that joint destruction might be progressing in patients in remission who show synovitis on MRI-MIP images.…”
Section: Discussionsupporting
confidence: 80%
“…It is a generally known and well-documented fact that hand function decreases in the course of RA [7–9]. Seyfried recorded a sixfold decrease in the strength of a hand affected by RA when compared with a healthy hand [10].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent rheumatoid thumb deformity is the type I (boutonniere) deformity [4] [5] [12]. It is initiated by proliferative MP joint synovitis bulging dorsally.…”
Section: Discussionmentioning
confidence: 99%